Calpain proteinase mRNA and beta-agonist induced muscle growth - Parr, Timothy (1991)
The mechanism by which β-agonists induce skeletal muscle hypertrophy is believed largely to be through a reduction in protein degradation. These growth promoters are also known to effect the activity of the calcium dependent proteinases (calpains) and their specific endogenous inhibitor calpastatin. The changes in activity appear to be toward a decrease in the calpain system's proteolytic potential. In this study attempts were made to determine whether the altered activity of the enzymes and inhibitor were brought about by induced changes in gene expression as reflected by altered levels of specific mRNAs.